Physiotherapy Management of Medial Meniscus Tear Using Ultrasound and Exercise Therapy to Improve Functional Ability - Fahreza Fatih Izzulhaq; Siti Nur Izzah; Shree Sharman (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to determine the effectiveness of physiotherapy management using Ultrasound, Transcutaneous Electrical Nerve Stimulation, and Exercise Therapy in reducing pain, increasing muscle strength, improving physical activity, and enhancing functional ability in patients with medial meniscus tear knee sinistra. Methodology: This study used a descriptive case study approach conducted at RSP Dr. Ario Wirawan Salatiga. The subject was one patient diagnosed with medial meniscus tear knee sinistra. Data collection techniques included observation, interview, and functional examination using Visual Analogue Scale (VAS), Manual Muscle Testing (MMT), and Knee Injury and Osteoarthritis Outcome Score (KOOS). Physiotherapy interventions included Ultrasound, Transcutaneous Electrical Nerve Stimulation, isometric exercise, and closed kinetic chain exercise. Main Findings: The results showed decreased pain intensity after four therapy sessions, with silent pain decreasing from 1 to 0, tenderness from 4 to 1, and movement pain from 5 to 2 based on VAS measurements. Muscle strength improved from grade 4 to 5 using MMT assessment. Functional ability also increased significantly, indicated by KOOS scores improving from 79% to 94% following physiotherapy interventions. Novelty/Originality of this study: This study integrates Ultrasound, Transcutaneous Electrical Nerve Stimulation, isometric exercise, and closed kinetic chain exercise in managing medial meniscus tear conditions. The study provides practical evidence regarding the combined effectiveness of electrotherapy and therapeutic exercise in improving pain reduction, muscle strength, and functional recovery among adolescent patients with knee meniscus injuries